2006
DOI: 10.1117/1.2198540
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the dynamic contact angle for conditions relevant to immersion lithography

Abstract: The semiconductor industry has used optical lithography to create impressively small features. However, the resolution of optical lithography is approaching limits based on light wavelength and numerical aperture. Immersion lithography is a means to extend the resolution by inserting a liquid with a high index of refraction between the lens and wafer. This enables the use of higher numerical aperture optics. Several engineering obstacles must be overcome before immersion lithography can be used on an industry-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Figure 14e shows the fast flow region that is nearby the rear trench of the immersion needle, where there still is a small reversed flow region. Schuetter et al (2006) and Riepen et al (2008) showed that the droplet tail becomes longer as long as the substrate speed increases. The size of the reversed flow region near the corner of the droplet is related to the length of the droplet tail.…”
Section: D Flow Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 14e shows the fast flow region that is nearby the rear trench of the immersion needle, where there still is a small reversed flow region. Schuetter et al (2006) and Riepen et al (2008) showed that the droplet tail becomes longer as long as the substrate speed increases. The size of the reversed flow region near the corner of the droplet is related to the length of the droplet tail.…”
Section: D Flow Fieldmentioning
confidence: 99%
“…To further increase yield, manufacturers of lithographic immersed-lens scanners wish to increase the wafer speed even further. Schuetter et al (2006) studied the transitions of the dynamic contact angle for the immersion droplet until the maximum substrate speed, about 0.4 m/s, where the droplet starts to break up. Riepen et al (2008) reported the evolution of dynamic contact angles as a function of the rotational speed where the substrate is rotated with respect to a liquid immersion droplet.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid-immersion lithography has the additional benefit of being compatible with much of the existing manufacturing infrastructure. Although liquid-immersion lithography is highly promising, several technical issues must be addressed regarding the contact of the fluid with the photoresist and mask [159,160], bubble formation [161], and local heating of the fluid during exposure [162].…”
Section: Photolithographymentioning
confidence: 99%
“…[5][6][7] In particular, topcoat polymer with high receding water contact angles allow rapid scanning of the immersion showerhead without film pulling. 8 The residual water left on the wafer after film pulling has been correlated with defectivity due to water marks and overlay error (due to evaporative cooling). [1][2] Achieving the delicate balance between the low surface energies required for high water contact angles (generally achieved via the incorporation of fluorinated groups) and the base solubility required for topcoat removal is challenging.…”
Section: Introductionmentioning
confidence: 99%